ACCURACY OF TWO IMPRESSION TECHNIQUES OF LOWER JAW WITH SINGLE REMAINING TEETH: CLINICAL TRIAL - Bratus-Hrynkiv Roksana Romanivna; Kordiyak A. Y (Romanian Society of Oral Rehabilitation, 2021)
Introduction. Digitization in daily dental practice is a challenging process and digital techniques are often limited to fabrication of the prostheses and not used in the clinical settings. The accuracy and reproducibility of virtual 3D printed and dental stone casts have not been clarified in full. Moreover, the impact of discrepancies between casts produced from modified and conventional impressions on the clinical performance of definitive restorations is still of considerable scientific and practical interest. Therefore, the purpose of this study was to make a comparison of conventional and modified impression techniques of lower jaw with single remaining teeth in terms of correctness and reproducibility of the basic prosthodontic procedures. Materials аnd methods. Five patients with mandibular single remaining teeth were included into the clinical trial. Definitive impressions were taken using open-mouth conventional impression technique (CIT) and closed-mouth modified impression technique (MIT). A total 10 dental stone casts obtained from the both techniques were digitized using a 3D laboratory model scanner and transferred to a dental 3-dimensional modeling software. Digital model images were superimposed and Distance Measurement Tool of Exocad software was used to evaluate dimensions between the marked points. Collected data were statistically analyzed by using Microsoft Excel software with non-parametric Wilcoxon-Mann-Whitney U test to determine results. Results and discussion. The present computer-aided clinical trial results indicated, that digital models created from CIT and MIT demonstrated dissimilar surface detail reproduction in particular denture foundation regions. Retromolar pads were the only relatively invariable parts of the basal seat with no divergence in cross section values. There was no significant variation of imprinting residual alveolar ridges (Z=0.119; p≤0,05) and vestibular side (Z =-0.1569; p≤0,05) overall by CIT and MIT regardless of the type of bone atrophy. Observing location of the lingual side peripheral tissues up to 4.7 mm deeper on the MIT in comparison to CIT-created models, confirmed by statistically significant (Z=3.3127; p≤0,05) difference in mandibular foundation surface z-score, was considered as important prerequisite for a better denture's border seal. Conclusions: 1. Combining functional impression taking and centric occlusion registration enables clinicians to integrate morphological and biomechanical factors of denture design and thus to customize prosthodontic procedures. 2. Results of digital analysis confirm higher model accuracy with respect to peripheral foundation tissues and buccal shelf region reproduction, obtained from closed-mouth modified impression technique under occlusal loading.